Observations of internal wave packets propagating along‐shelf in northern Monterey Bay - Woodson, C. B. (2017)
Internal waves of depression were observed propagating along‐shelf and into northern Monterey Bay, California (CA) on the inner shelf. These waves had amplitudes approximately equal to the thermocline depth (∼4 m), and were unstable to shear and mix the thermocline. Isopycnal gradient spectra showed that the wave packets lead to an elevated mean dissipation rate of " = 2.63 × 10−5 m3 s−2 for up to 2 hours after wave passage. The proximity to the surface created strong surface convergences that can actively transport buoyant material, such as plankton, back into the bay. The wave packets were observed regularly over the upwelling season across multiple years suggesting they may have large effects on the documented spatial variation of phytoplankton and larvae on the inner shelf. The timing of the waves suggests they are not formed by tides interacting with bathymetry, but are generated by buoyant plume propagation.